Easy method of centralized fixation of endotracheal tube in cleft lip and palate surgery - S. P. Bajaj; Navdeep Chavan; Arun Sharma (Indian Journal of Plastic Surgery)
As we all know that fixation of endotracheal tube is very important aspect in cleft palate and maxillofacial surgery. During cleft palate and oral surgery various methods of fixation and modified tubes are deviced to make surgery safer and ergonomically better. Our method consist of 3 point fixation of tube (RAE) with dynaplast, which is freely available, cheap and good Adhesive quality. Dynaplast divided into 3 phalanges (one central and two lateral) and one portion undivided as central limb. This undivided central limb is fixed in centre of chin and other 3 phalanges wrap around tube on either side. This fixation totally takes away any lateral movements of tube. This method can be used with any tube (RAE/ Oxford/Flexometallic). Our method is described for its simplicity, ease and convinence and result which impart universally similar results with all different members of our anesthetist team.